Fighting for wilderness : papers from the Australian Conservation Foundation's Third National Wilderness Conference, 1983 - Mosley, J. G. (John Geoffrey), 1931-; Messer, J. (Fontana ; ACF, 1984)
Includes papers by Strider and A.M. Fox annotated separately.